Tachy- and bradyarrhythmia as an initial presentation of human immunodeficiency virus-related primary cardiac lymphoma: a case report. Issue 4 (4th December 2019) - Ng, Shonda; Krisnadi, Cindy; Low, Randal Jun Bang; Yew, Min Sen
Abstract: Background: Primary cardiac lymphoma is defined as extranodal lymphoma involving the heart or pericardium. Common presentations of human immunodeficiency virus (HIV)-associated cardiac lymphoma include heart failure, cardiac tamponade, and rhythm abnormalities. Arrhythmia is an uncommon presentation and treatment in young HIV patients is particularly challenging. We present a unique case of primary cardiac lymphoma in an HIV patient presenting with both symptomatic tachy- and bradyarrhythmias. Case summary: A 27-year-old man presented with intermittent palpitations and chest pain for 2 weeks. He has a significant past history of advanced HIV. He was noted to have complete heart block on cardiac monitoring. Imaging showed a large mass in the right atrioventricular (AV) groove extending into the myocardium, associated with a moderate pericardial effusion. During his stay, he developed symptomatic tachy–brady arrhythmias, with intermittent junctional tachycardia, supraventricular tachycardia, and complete AV block. After a multidisciplinary team discussion, endomyocardial biopsy was performed under fluoroscopy and transthoracic echocardiography guidance. Histology from the interventricular septum was consistent with Epstein–Barr virus positive B-cell lymphoma. The patient was subsequently transferred to a tertiary hospital with cardiothoracic surgical support to initiate chemotherapy. Discussion: To our knowledge, our patient is the first reported case of HIV-related primary cardiac lymphoma presenting with palpitations secondary to paroxysmal supraventricular tachycardia with concomitant AV block. This case illustrates the utility of multi-modality imaging in the investigation of a cardiac mass and the importance of having a high index of suspicion for pathology, such as cardiac lymphoma in HIV patients complaining of apparently minor cardiac complaints.